A Prospective Randomized Clinical Trial in Total Hip Arthroplasty—Comparing Early Results Between the Direct Anterior Approach and the Posterior Approach - Cheng, Tze E.; Wallis, Jason A.; Taylor, Nicholas F.; Holden, Chris T.; Marks, Paul; Smith, Catherine L.; Armstrong, Michael S.; Singh, Parminder J. (The Journal of arthroplasty, 2017)
We report a prospective randomized study comparing early clinical results between the direct anterior approach (DAA) and posterior approach (PA) in primary hip arthroplasty. Surgeries were performed by 2 senior hip arthroplasty surgeons. Seventy-two patients with complete data were assessed preoperatively 2, 6, and 12 weeks postoperatively. The primary outcomes were the Western Ontario McMasters Arthritis Index and Oxford Hip Scores. Secondary outcome measures included the EuroQoL, 10-meter walk test, and clinical and radiographic parameters. Data analyses showed no difference between DAA (n = 35) and PA (n = 37) groups when comparing total scores for primary outcomes. No significant differences were observed for 10-meter walk test, EuroQoL, and radiographic analyses. Subgroup analysis for surgeon 1 identified that the DAA group had shorter acute hospital stay, less postoperative opiate requirements, and smaller wounds. However, this was offset by increased operative time, higher intraoperative blood loss, and weaker hip flexion at 2 and 6 weeks. Subgroup analysis of items on the Western Ontario McMasters Arthritis Index and Oxford Hip Score identified that hip flexion activity favored the DAA group up to 6 weeks postoperatively. There was an 83% incidence of lateral cutaneous nerve of thigh neuropraxia at the 12-week mark in the DAA group. No neuropraxias occurred in the PA group. One dislocation occurred in each group. A single patient from the DAA group required reoperation for leg-length discrepancy. DAA total hip arthroplasty (THA) has comparable results with PA THA. Choice of surgical approach for THA should be based on patient factors, surgeon preference, and experience.